Scientific Literacy Skill in Science Learning based on Ethnoscience - Yasir, Mochammad; Annuria Auliya Rahma; Mubarok, Husni; Zakaria, Nurul Sabihah (Universitas Tidar, 2024)
Science literacy is very much needed in the future because it encourages students to solve problems and investigate scientifically. However, students' science literacy is currently still low, resulting in environmental ignorance. Students' low science literacy is attempted to be improved by conducting ethnoscience-based science learning by integrating environmental problems, science materials, and scientifically tested community knowledge. This study aims to determine the differences in science literacy abilities in ethnoscience-based science learning. This type of research is Pre Experimental research with a One Group Pretest-Posttest design. The research was conducted in the even semester of the 2023/2024 academic year at SMP Al Hikam Burneh. The research population was all students of class VII. The sample used was class VII-B as many as 22 students who were taken using the Purposive Sampling technique based on teacher recommendations regarding student abilities. The research instrument used was a science literacy test consisting of 6 essay questions. The data collection method used a test. The data analysis technique used descriptive statistics and paired sample t-test. The results of the study obtained (1) the average value of the pretest of students' scientific literacy skills was 53.00 and the posttest was 79.98; and (2) the results of the paired sample t-test were –12,978 2,079 11,878 which showed that students' scientific literacy skills experienced differences after ethnoscience-based science learning. It can be concluded that there are differences in students' scientific literacy skills in ethnoscience-based science learning.